Semi-Transparent Energy-Harvesting Solar Concentrator Windows Employing Infrared Transmission-Enhanced Glass and Large-Area Microstructured Diffractive Elements - Mikhail Vasiliev; Kamal Alameh; Mohsin Ali Badshah; Seok-Min Kim; Mohammad Nur-E-Alam (Photonics, 2018)
We report on the study of energy-harvesting performance in medium-size (400 cm2) glass-based semitransparent solar concentrators employing edge-mounted photovoltaic modules. Systems using several different types of glazing system architecture and containing embedded diffractive structures are prepared and characterized. The technological approaches to the rapid manufacture of large-area diffractive elements suitable for use in solar window-type concentrators are described. These elements enable the internal deflection and partial trapping of light inside glass-based concentrator windows. We focus on uncovering the potential of pattern-transfer polymer-based soft lithography for enabling both the improved photon collection probability at solar cell surfaces, and the up-scaling of semitransparent solar window dimensions. Results of photovoltaic characterization of several solar concentrators employing different internal glazing-system structure and diffractive elements produced using different technologies are reported and discussed.